Pemilihan Peserta Lomba Kompetensi Siswa Menggunakan Metode TOPSIS - Maulia Rahman; Jufriadif Na’am; Julius Santony (Universitas Putra Indonesia YPTK Padang, 2018)
Vocational High School Student Competency Competition (Vocational School LKS) is a series of activities conducted by the Education Office. This activity is carried out as one of the means and ways to measure the success of the education process in Vocational Schools. LKS is held as a vehicle for competition in promoting students' abilities to the business world and industry. For the determination of the winning contestants correctly and precisely requires a good decision system. The method that used in this study is TOPSIS on report card grades in 2018. The results of this study are participants who qualify with a value of V = 0.7978. Participants who qualify for this place rank first in the match with 80% conformity to the participants sent in the match. So that this method is a recommendation to dismiss the process of determining the next LKS contest participant.